A fluorescent sensor based on ovalbumin-modified Au nanoclusters for sensitive detection of ascorbic acid. Issue 10 (21st May 2015) - Li, Yanxia; Chen, Yiting; Huang, Lu; Ma, Liang; Lin, Qi; Chen, Guonan
<x xml:space="preserve">Abstract</x> In this paper, ovalbumin (OVA) stabilized gold nanoclusters (OVA-Au NCs) were used as sensing probes for ascorbic acid (AA) detection.